NORMATIVE LEGAL DOCUMENTS REGULATING INTERNATIONAL COOPERATION IN THE FIELD OF EDUCATION ON THE BASIS OF REGIONAL AND BILATERAL AGREEMENTS - Nomanjonov Khudoberdi Abdubakir ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This scientific article considers the importance of legal documents based on regional and bilateral agreements to be higher than universal legal documents in the activities of international cooperation in the field of education.